Ga-68-Prostate-Specific Membrane Antigen PET-Positive Paget Bone Disease With Metastatic Prostatic Carcinoma - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2020)
Paget bone disease is a chronic benign bone disease characterized by excessive and abnormal bone remodeling. The scintigraphic and bone SPECT/CT hybrid imaging appearances of the affected bone(s) depend on the stage of the disease. We report the case of a patient newly diagnosed with prostate cancer who was found to have multiple osseous metastases, with coexisting Paget disease in the left hemipelvis diagnosed because of typical scintigraphic and SPECT/CT appearance.Ga-68-prostate-specific membrane antigen PET/CT was also performed for initial staging. Pagetoid bones showed increased prostate-specific membrane antigen uptake like skeletal metastases.
Keywords: Paget disease of bone; Tc-99m-methylene diphosphonate bone scintigraphy; prostate cancer; bone metastases; SPECT-CT (single photon emission computerized tomography/computed tomography); Ga-68-PSMA PET-CT; POTENTIAL-PITFALL; (68)GA-PSMA; FRACTURE; PATIENT